The healing of America - Williamson, Marianne 1952- (New York, NY Simon & Schuster, 1997)
Noting a spiritually motivated political activism now emerging in America, Marianne Williamson claims that traditional political activists increasingly look to spiritual wisdom for inspiration while spiritual contemplatives are increasingly eager to extend their service to the world into political realms. The convergence of the two impulses forms what Williamson calls a "holistic politics."

With the publication of The Healing of America, Williamson becomes a powerful voice for social conscience in American society. While citing the virtual abandonment of social justice as a dominant political theme since the 1960's, Williamson notes historian Arthur Schlesinger's contention that Americans express renewed political interest every thirty years. This is a time, according to Williamson, for Americans to return once again to our first principles -- political and spiritual. In this landmark work, Williamson draws plans for the transformation of American political consciousness and the reemergence of powerful citizen involvement in a genuine healing of American society.
Includes bibliographical references (pages 345-346) and index.
Keywords: Spirituality -- United States; Religion and culture -- United States; Religion and politics -- United States; United States -- Religion